Macroevolutionary processes in turtles (Testudines): a view from biomic specialization and historical climatic changes - Thomas, Juan S.; Gamboa, Sara; Hernández Fernández, Manuel; Murillo, Oscar; Pelegrin, Jonathan S. (Frontiers in Ecology and Evolution, 2024)
The resource-use hypothesis proposed by Elisabeth S. Vrba suggests that lineages display varying tendencies toward generalism or specialization in biome occupancy, with a tendency towards the accumulation of specialists due to their higher rate of speciation through vicariance. It also posits differences in biome occupancy patterns driven by the environmental characteristics of biomes, with a higher presence of biome specialist species in biomes that are placed in the extremes of the global climatic gradients. Here, we tested this hypothesis in turtles, a very ancient and morphologically stable lineage, representing a remarkable diversity with 357 species, many of which are threatened with extinction. We analyzed the resource-use hypothesis in a phylogenetic context within the Testudines lineage. For this purpose, a presence/absence matrix was compiled for all species across all 10 terrestrial biomes. Their distribution across biomes was contrasted with 10,000 Monte Carlo simulations. The relationship between diversification rates and both the biomic specialization index and the biomes occupied by specialists species was evaluated. The results demonstrate strong consistency with Vrba`s hypothesis, revealing a higher number of biome specialist species than expected by chance, with a significant accumulation of species in tropical ecosystems. These trends also were observed for ecological groups (terrestrial and freshwater species). In addition, higher diversification rates were observed for biome specialist species, although the particular biome occupied did not significantly influence their diversification rates.